CREATIVE STUDENT DAY PROGRAM MANAGEMENT IN DEVELOPING STUDENT’S TALENTS INTERESTS - Nurmayuli; Afda, Miranti Adelia (Idaarah: Jurnal Manajemen Pendidikan, 2023)
The development of talents and interests are very essential factor in determining the success of education. One of goals of Creative Student Day program is to create the student being creative. Madrasah Aliyah Salafiyah Darul Muta’allimin in the context of developing the talents and interests of the students also made a Creative Student Day program or also known as the santri musabaqah such as calligraphy, speech in three languages, fahmil Qur’an, and reading the yellow book. The purpose of this study was to determine the planning, implementation, and evaluation of the Creative Student Day program in developing the talents and interests of students at Madrasah Aliyah Salafiyah Darul Mut’allimin Tanah Merah Aceh Singkil. This study utilizes descriptive qualitative research methods using observation, documentation, and interviews. The Creative Student Day program has succeeded in developing talents therefore students have competitiveness, hone skills, and achievements when participating in competitions.